Existential aspects of fatherhood transition—A systematic qualitative review protocol using framework synthesis - Marie Sejrsgaard; Caroline Moos; Maiken Fabricius Damm; Christina Prinds (PLoS ONE, 2025)
Background Research on the experiences of parenthood transition has previously primarily focused on the mother/birthing woman. Even with an expanding interest in the existential aspects of health in relation to becoming a parent, the experiences of the fathers are often overlooked, as in a 2014 scoping review exploring the existential meaning-making of becoming a mother. With changing expectations of the role of fatherhood, a greater understanding of the experiences of fathers is required, and a specific focus on the existential aspects could add valuable insight into changes in identity, values, and notions of a good life among new and expecting fathers. Methods and analysis This systematic qualitative review protocol maps out a plan to explore existing knowledge on the existential aspects of becoming a father through a Framework Synthesis using Peter la Cours model of existential health. Five databases (MEDLINE, Embase, PsycINFO, CINAHL and Web of Science) will be searched from 01.01.2010 to the present day. Two independent, blinded reviewers will assess the eligibility of included studies according to the listed inclusion and exclusion criteria. The Critical Appraisal Skills Program (CASP) checklist will be utilized to assess the methodological quality of the included studies. Additionally, Web of Science will be used for snowball searching of included references. Conclusion and dissemination The findings from this synthesis may contribute to development of evidence-informed clinical guidelines that promote person-centred and father-inclusive maternal care.The findings will be disseminated in peer-reviewed journals, conferences, and social media. Registration The study protocol has been registered with the International Platform for Prospective Registration of Systematic Reviews (PROSPERO), with registration number: CRD420251038896.